Bibliometric Mapping Analysis of the Cyberbullying Phenomenon Among Children - Laila Fatmawati; Haryanto Haryanto (Proceedings Series on Social Sciences & Humanities, 2023)
Cyberbullying has become a global problem. This phenomenon is not only a trend among teenagers, but has penetrated among children. The impact is felt so significantly by both perpetrators and victims of cyberbullying. The purpose of this study is to map the trend of the cyberbullying phenomenon among children over the past decade. Data search through data-based Scopus with keywords "cyberbullying" and "children", during 2014-2023. The results showed that searching for articles using keywords resulted in 1,001 articles from journals and conference papers only. The development of cyberbullying reality publications experienced the highest increase in 2019 by 14.23%. The largest subject areas are medicine and psychology. This provides an opportunity in the field of education, that the theme of cyberbullying and its impact on the field of education still needs to be deepened in research and publication.